2010
DOI: 10.1039/b927248h
|View full text |Cite
|
Sign up to set email alerts
|

Easy oxidatively induced silicon–carbon bond activation in organoplatinum chemistry

Abstract: The oxidation of the complex [PtMe(2)(bps)], bps = bis(2-pyridyl)dimethylsilane, by oxygen, hydrogen peroxide or dibenzoyl peroxide in the presence of water or alcohol gives the complex cation, [PtMe(3)(kappa(3)-N,N,O-HOSiMe(2-C(5)H(4)N)(2))](+), in a reaction involving easy cleavage of a methylsilicon bond.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…Noteworthy activation processes have also been documented by Puddephatt's group, who reported on the cleavage of C aryl −S bonds by [PtMe 2 (dimethylsulfide)] 2 leading to polymethylated SMe − bridged bimetallic compounds . Carbon–silicon bond activation under oxidative conditions has also been described …”
Section: Synthesis and Structures: A Systematic Overview Of D‐block Ementioning
confidence: 70%
“…Noteworthy activation processes have also been documented by Puddephatt's group, who reported on the cleavage of C aryl −S bonds by [PtMe 2 (dimethylsulfide)] 2 leading to polymethylated SMe − bridged bimetallic compounds . Carbon–silicon bond activation under oxidative conditions has also been described …”
Section: Synthesis and Structures: A Systematic Overview Of D‐block Ementioning
confidence: 70%
“…Puddephatt et al reported a related oxidation involving SiÀ C bond cleavage. [102] [94,96,97] and NNO-ligated [98] Pt II complexes. Scheme 18.…”
Section: Aerobic Oxidation Of Pt II Complexes To Pt Ivmentioning
confidence: 99%
“…Puddephatt et al. reported a related oxidation involving SiC bond cleavage 102. Adding O 2 to a solution of [(bps)PtMe 2 ] ( 73 , bps=Me 2 Si(2‐C 5 H 4 N) 2 , Scheme ) in MeOH resulted in the formation of [(HOSiMe(2‐C 5 H 4 N) 2 )PtMe 3 ][OMe] ( 74 ).…”
Section: Stoichiometric Reactions Of Ptii With O2mentioning
confidence: 99%
“…In this regard, the metal catalyzed hydrolysis and alcoholysis of hydrosilanes is well‐established, and examples of similar oxidation at Si have been reported involving hydrolysis of PSiP‐supported complexes in the absence of O 2 (Figure , K – L ) , . Lastly, an intriguing related example of oxidation at Si was reported by Puddephatt and co‐workers for a Pt II ‐dimethyl complex supported by bis(2‐pyridyl)‐dimethylsilane (bps). Oxidation of (bps)PtMe 2 with oxygen/MeOH occurs with cleavage of a Me–Si bond to afford a Pt IV ‐siloxy species (Figure , I ).…”
Section: Resultsmentioning
confidence: 68%
“…Moreover, the observation of multiple unidentified products in this reaction further complicates the mechanistic possibilities . By comparison, Puddephatt and co‐workers propose that the siloxane I (Figure ) is formed by a pathway involving initial formation of a hydroperoxo Pt IV cation with a methoxide anion, which reacts rapidly with a second molecule of (bps)PtMe 2 to form a cationic Pt IV ‐hydroxo complex with a methoxide anion. Nucleophilic attack of the methoxide group at Si and methyl group transfer to Pt, followed by the displacement of the methoxy group from Si by the Pt‐OH group affords the product I with elimination of methanol.…”
Section: Resultsmentioning
confidence: 99%